Performance of Perennial Medicinal Crops in Poplar Based Three Tier Agroforestry System - Kumari, Bimlendra; Madan, V. K. (Indian Forester, 2016)
Poplar based agroforestry systems have been conveniently adopted by the farmers of India because of the several advantages associated with the tree. Poplar tree is known to cause a negligible effect on the intercrops during the first three years of growth. However after three-year growth of trees, intercultural crop productivity declines significantly. Taking these into consideration four perennial medicinal plants viz: Glycyrrhyza glabra (mulathi), Asparagus racemosus (shatawari), Aloe vera (gwarpatha), and Tinospora cordifolia (giloe) were planted with poplar trees. Poplar trees were planted at three spacing i.e 5x4 m, 10x2 m and 18x2x2 m (paired row) in completely randomized block design with three replications each. Gwarpatha and Mulathi were planted as intercrops in between the tree lines in all the tree spacings, giloe and shatawari (climber type of medicinal plants), were grown on tree stems, thus making the system a three tier one. The medicinal crops grew significantly better in terms of growth parameters in close spacings of poplar i.e. 5x4 m and 10x2 m as compared to the wider spacing of 18x2x2 m and control. Yield of three out of four crops was maximum in 5x4 m spacing (145 t/ha. in gwarpatha, 14.76 t/ha. in giloe, 0.37 t/h in mulathi) and decreased significantly in wider spacing and control, however in shatawari the dry yield was 1.8 t/ha. in 5x4 m and 10x2 m spacing, however the gel content/ leaf was significantly less in the closer spacings. Quality parameters such as the total crude glycirrhizin content for shatawari, the mucilage percentage and Aloin content of gwarpatha the total bitter content for Giloe, Saponin content for shatawari was significantly more in 5x4m spacing of poplar, as compared to wider spacing's and control.